Complete metamorphic cycle and long‐lived anatexis in the c. 2.1 Ga Mistinibi Complex, Canada. (23rd January 2020) - Godet, Antoine; Guilmette, Carl; Labrousse, Loic; Davis, Donald W.; Smit, Matthijs A.; Cutts, Jamie A.; Vanier, Marc‐Antoine; Lafrance, Isabelle; Charette, Benoit
Abstract: Secular changes in the architecture, thermal state, and metamorphic style of global orogens are thought to have occurred since the Archean; however, despite widespread research, the driving mechanisms for such changes remain unclear. The Paleoproterozoic may prove to be a key era for investigating secular changes in global orogens, as it marks the earliest stage of an eon that saw the onset of modern‐style global tectonics. The 2.1 Ga granulite‐facies Mistinibi‐Raude Domain (MRD), located in the Southeastern Churchill Province, Canada, offers a rare exposure of Paleoproterozoic high metamorphic grade supracrustal sequences (Mistinibi Complex, MC). Rocks from this domain were subjected to petrochronological investigations to establish P – T – t – X evolutions and to provide first order thermal state, burial and exhumation rates, and metamorphic gradients for the transient Paleoproterozoic times. To obtain comprehensive insight into the P – T – t – X evolution of the MRD, we used multi‐method geochronology—Lu–Hf on garnet and U–Pb on zircon and monazite—integrated with detailed petrography, trace element chemistry, and phase equilibria modelling. Despite the extensive use of zircon and monazite as geochronometers, their behaviour in anatectic conditions is complex, leading to substantial ambiguity in interpreting the timing of prograde metamorphism. Our results indicate a clockwise metamorphic path involving significant melt extraction from the metasedimentary rocks, followed by cooling from >815°C to ~770°C at ~0.8 GPa. The timing of prograde burial and cooling from supra‐ to subsolidus conditions is constrained through garnet, monazite, and zircon petrochronology at 2, 150–2, 120 Ma and at 2, 070–2, 080 Ma, respectively. These results highlight long‐lived residence of the rocks at mid‐crustal supra‐solidus conditions (55–70 Ma), with preserved prograde and retrograde supra‐solidus monazite and zircon. The rocks record extremely slow burial rates (0.25–0.30 km/Ma) along a high metamorphic gradient (900–1, 000°C/GPa), which appears symptomatic of Paleoproterozoic orogens. The MC did not record any significant metamorphism after 2, 067 Ma, despite having collided with terranes that record high‐grade metamorphism during the major 1.9–1.8 Ga Trans‐Hudson orogeny. The MC would therefore represent a remnant of a local early Paleoproterozoic metamorphic infrastructure, later preserved as superstructure in the large hot Trans‐Hudson orogen.